UPAYA MENINGKATKAN AKTIVITAS BELAJAR MATEMATIKA MENGGUNAKAN PENDEKATAN MATEMATIKA REALISTIK BERBANTUAN MEDIA KARMILA - Rospala Rospala Hanisah Yukti Sari; Navis Shofian Aristi (EMTEKA: Jurnal Pendidikan Matematika, 2024)
The majority of mathematics learning currently carried out still uses the lecture method so that mathematics learning is meaningless and passive. Therefore, it is important to apply a Realistic Mathematics Approach so that learning mathematics becomes more enjoyable and meaningful. The subjects of this research were students in class IV B at SD Negeri 6 Palangkaraya, totaling 23 students. The aim of this research is to increase students' mathematics learning activities by using a Realistic Mathematics approach assisted by KARMILA media. The type of research used is Classroom Action Research (PTK). The research method used is a mix method, which is a combination of qualitative and quantitative. The data analysis techniques used are reduction, data presentation and drawing conclusions. The research results showed that students' activities when taking action using the Realistic Mathematics Approach assisted by KARMILA media in class IV B of SD Negeri 6 Palangka achieved good criteria. This can be seen from the results of observations made by observers when learning takes place. In cycle I, student activities obtained an average score of 3.7 with good criteria, while in cycle II, student activities received an average score of 3.95 with good criteria. So, it can be concluded that using the Realistic Mathematics Approach assisted by KARMILA media has been proven to increase the learning activities of class IV B students at SD Negeri 6 Palangkaraya.